Venture Capital in Japan: A Financial Instrument Supporting the Innovativeness of the Japanese Economy - Młodawska, Jolanta (Comparative Economic Research. Central and Eastern Europe, 2012)
Venture capital (literally “high–risk capital”) is designated for the financing of small companies that by themselves lack sufficient resources, but whose activities indicate potentially high profits in the future. It can play a special role in the development of the technologically advanced industries as well as in the growth of entrepreneurship understood as a readiness to establish new companies (“start–ups”). Two factors: First, the relatively small number of new companies as well as the number of companies subject to liquidation over the year (“firm turnover”) in Japan, and second, the insignificant prestige associated with the profession of entrepreneur do not foster growth in the dynamics of this form of financing ventures. The cited indicator for Japan in among the lowest in comparison with other highly developed countries1, while the profession of entrepreneur is not the foremost dream of college graduates. They would much rather prefer realizing their professional careers as members of the government bureaucracy or employees of a major corporation2. However, this mindset is slowly changing, if for no other reason then, in spite of popular conviction, because most small companies are not established during periods of prosperity, but near the end of the downward phase of the economic cycle. That is exactly the phase Japan has been dealing with for several years now. Young, creative people, recruited from the unemployed, are seeking self–employment, using all possible opportunities embedded in the “again starting up” machinery of the economy.